(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Change detection of building from high-resolution remote sensing images is an important and challenging research field in remote sensing. In this paper a novel technique for building change detection from remote sensing imagery is presented. First, The Morphological Building Index (MBI) features values are computed for each of the pair images from our datasets and then change of these two MBI images is measured to indicate the building change. For evaluation purpose, the experiments are carried on IKONOS and Quick Bird images. The results show that the proposed technique can attain acceptable correctness rates above 90% with overall errors fewer than 9%. Compared with state-of-the-art methods in building change detection; the proposed framework is computationally much more efficient while achieving better performance in terms of correctness, completeness, and quality.